2016
DOI: 10.1155/2016/4275148
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Status and Anthropometric Indices in High School Girls in Ilam, West Iran

Abstract: Background. Adolescence is one of the most challenging periods for human growth and nutritional status. The aim of this study was to assess the nutritional status and anthropometric indices in high school girls in Ilam. Methods. This cross-sectional study was performed on 360 domestic high school girl students chosen randomly by cluster sampling. Data were gathered through interviews performed by a dietitian to fill 24-hour dietary recall and food frequency and demographic questionnaires. Then we performed the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…The sources of energy for adolescents in middle-and lowincome countries particularly for adolescents from low socioeconomic status were restricted to a repetitive consumption of limited staples (6)(7)(8) . The Ethiopian national food consumption survey also reported that a monotonous diet in households was common across different regions (9) .…”
Section: Introductionmentioning
confidence: 99%
“…The sources of energy for adolescents in middle-and lowincome countries particularly for adolescents from low socioeconomic status were restricted to a repetitive consumption of limited staples (6)(7)(8) . The Ethiopian national food consumption survey also reported that a monotonous diet in households was common across different regions (9) .…”
Section: Introductionmentioning
confidence: 99%
“…Astini reported that the prevalence of malnutrition among adolescents (aged 10–19 years) in Bali in 2013 was underweight (48.6%), overweight (8.7%), and obese (1.1%) 7 . Research in Iran confirms the prevalence of being underweight among young girls in high school 15 ; a study in Malaysia found the prevalence of being underweight among adults in Malaysia was 9.8% 16 ; and research in Ekiti State, Nigeria verified the prevalence of being underweight as 11.7% 17 . Finally, research in Bijnor district of Uttar Pradesh, India confirmed that 35% of adolescents were underweight 18…”
Section: Discussionmentioning
confidence: 91%
“…prevalence of zinc deficiency (Levitt et al, 2010) quacy (i.e., vitamin B9, calcium, magnesium, and zinc) to be associated with food insecurity (Jamalikandazi et al, 2016;Kirkpatrick & Tarasuk, 2008;M'Kaibi et al, 2015). In comparison with the existing literature, a study (Beyene, 2023) highlighted the adverse effects of food insecurity on health outcomes, emphasizing the importance of food security and nutrition in improving health outcomes.…”
Section: Discussionmentioning
confidence: 99%